Foliar and Seed Application of Amino Acids Affects the Antioxidant Metabolism of the Soybean Crop - Teixeira, Walquíria F.; Fagan, Evandro B.; Soares, Luís H.; Umburanas, Renan C.; Reichardt, Klaus; Neto, Durval D. (Frontiers in Plant Science, 2017)
In recent years, the application of natural substances on crops has been intensified in order to increase the resistance and yield of the soybean crop. Among these products are included plant biostimulants that may contain algae extracts, amino acids, and plant regulators in their composition. However, there is little information on the isolated effect of each of these constituents. The objective of this research was to evaluate the effect of the application of isolated amino acids on the antioxidant metabolism of the soybean crop. Experiments were carried out in a greenhouse and in the field with the application of the amino acids glutamate, phenylalanine, cysteine, glycine in seed treatment, and foliar application at V4 growth stage. Antioxidant metabolism constituents evaluated were superoxide dismutase, catalase, peroxidase, hydrogen peroxide content, proline, and lipid peroxidation. In addition, resistance enzymes as polyphenol oxidase and phenylalanine ammonia-lyase (PAL) were evaluated. In both experiments, the use of cysteine, only in seed treatment and in both seed treatment and foliar application increased the activity of the enzyme PAL and catalase. Also in both experiments, the use of phenylalanine increased the activity of the enzyme PAL when the application was carried out as foliar application or both in seed treatment and foliar application. In the field experiment, the application of glutamate led to an increase in the activity of the catalase and PAL enzymes for seed treatment and foliar application. The use of the set of amino acids was only efficient in foliar application, which led to a greater activity of the enzymes peroxidase, PAL, and polyphenol oxidase. The other enzymes as well as lipid peroxidation and hydrogen peroxide presented different results according to the experiment. Therefore, glutamate, cysteine, phenylalanine, and glycine can act as signaling amino acids in soybean plants, since small doses are enough to increase the activity of the antioxidant enzymes.